Pengembangan Alat Skrining Potensi Gangguan Psikologis pada Mahasiswa: Uji Validitas dan Reliabilitas - Arrumaisha Fitri (Psychospiritual: Journal of Trends in Islamic Psychological Research, 2026)
This study aims to develop a screening tool for potential psychological disorders in college students and test its validity and reliability. The research method employed is quantitative, utilizing a measurement tool development approach grounded in psychometric principles. The measurement tool was developed based on three aspects: severe psychological problems, general psychological problems, and potential psychological disorders (academic, social, and family pressure). Content validity was calculated using the Aiken's V index, while reliability was estimated using the Cronbach's Alpha coefficient. Expert testing on 5 psychologists and item trials on 128 college students. The results showed that all items had an Aiken's V value > 0.40, with 54 items (55.7%) in the very high category (V ≥ 0.80). The trial on the aspect of potential psychological disorders (43 items) resulted in all items being valid (r > 0.173) and reliable (α = 0.94). The screening tool for potential psychological disorders has adequate content validity and reliability, making it suitable for use as an instrument for early identification of potential psychological disorders in college students.